ANALISIS POTENSI SUMBER DAYA ALAM TERHADAP PENINGKATAN PERTUMBUHAN EKONOMI DI PROVINSI JAWA TIMUR - Dede Salwa Oktavia; Devy Sinta Sari, Gusnandi Setiwan, Nana Talia, Sopia Grace Silaban, Suherman (Jurnal Ekonomi dan Bisnis, 2024)
This research aims to analyze the relationship between natural resource potential and economic growth in East Java Province. This province has a variety of natural resources, including agriculture, fisheries, creative industries and other natural potential. In this context, it is important to understand how natural resources can make a significant contribution to regional economic growth. The analytical method used in this research is a quantitative method, by collecting economic data and information on natural resource potential from various sources. The collected data was then analyzed using statistical methods and multiple regression analysis techniques using the IBM SPSS 22 program to find the relationship between natural resource potential and economic growth in East Java Province. The results of this research show that natural resource potential in East Java Province has an influence which is not significant to economic growth in East Java Province. This research provides a deeper understanding of the importance of sustainable natural resource management and utilization of existing natural potential. The implication of this research is that the existence of policies that support the development of natural resource-based economic sectors can accelerate the economic growth of East Java Province as a whole.